2023
DOI: 10.3390/healthcare11182561
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation Intervention in Transitional Care for People with COVID-19: Pre-Post Study with a Non-Equivalent Control Group

Neuza Reis,
Maria José Costa Dias,
Luís Sousa
et al.

Abstract: SARS-CoV-2 infection and its resulting sequelae have increased the prevalence of people with respiratory symptoms, with impacts on functional capacity, quality of life, anxiety, depression, and mental health. To mitigate this problem, one challenge has been the design and implementation of interventions that simultaneously allow for education, rehabilitation, and monitoring of people with long COVID, at a time when health services were on the verge of rupture due to the volume of people with active COVID and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Although the research strategy was comprehensive in answering the research question, the low number of studies identified stands out for showing that telerehabilitation is still in development and being adopted by reference centres for monitoring the disease, still without dissemination of the results of its implementation. Even so, the results corroborate the opinions of other authors, who suggest that supervised telerehabilitation with telemon-itoring support is feasible and safe, without adverse events, and adherence is high, with a recruitment rate consistent with previous respiratory rehabilitation trials [30,31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the research strategy was comprehensive in answering the research question, the low number of studies identified stands out for showing that telerehabilitation is still in development and being adopted by reference centres for monitoring the disease, still without dissemination of the results of its implementation. Even so, the results corroborate the opinions of other authors, who suggest that supervised telerehabilitation with telemon-itoring support is feasible and safe, without adverse events, and adherence is high, with a recruitment rate consistent with previous respiratory rehabilitation trials [30,31].…”
Section: Discussionsupporting
confidence: 89%
“…These virtual interventions eliminate the need for unnecessary in-person referrals to specialists, reduce wait times for specialist feedback, and eliminate the need for unnecessary travel [32]. They also simultaneously allow the timely identification of clinical changes, worsening of symptoms, and non-adherence to the therapeutic regimen [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“… Reis et al (2023) , explored the pre-post effects of telerehabilitation (i.e., a home-based rehabilitation program supervised by video calls) in patients with Long COVID in control and intervention groups. The intervention group received an intensive rehabilitation program three times a week for 12 weeks followed by a maintenance rehabilitation phase once a week for 2 weeks.…”
mentioning
confidence: 99%